Management of the two-spotted spider mite, Tetranychus urticae [Acari: Tetranychidae] in eggplant fields - Bostanian, Noubar; Trudeau, Martin; Lasnier, Jacques (Phytoprotection, 2003)
SummaryA three-season field evaluation showed that eggplants (Solanum melongena) are very tolerant to damage caused by the two-spotted spider mite, Tetranychus urticae. Although large numbers of the predacious mites, Neoseiulus fallacis or Phytoseiulus persimilis were released, biological control of the two-spotted spider mite could not be sustained in the field. Based on a preliminary comparison of yield in both sprayed and unsprayed plots and on a three-year qualitative assessment, a tentative action threshold of 600 two-spotted spider mites per leaf would not decrease yield and would reduce the number of acaricide treatments per season. The new acaricide spirodiclofen was effective against the two-spotted spider mite in a preliminary trial.